FDI and Human Capital: Gender Effects and Education Spillovers in European Union - Kottaridi, Constantina; Louloudi, Konstantina (SPOUDAI Journal of Economics and Business, 2023)
The objective of the present paper is to examine how gender education disparities and democracy shape inward FDI in EU countries. We basically build upon Dunning’s and Lundan (2008) extension of determinants of FDI including policy-induced effects generated by institutions by incorporating institutional effects (gender education disparities) as a significant location factor. Specifically, we investigate how the location behavior of Multinational Enterprises (MNEs) is shaped by gender educational disparities in EU countries. Since the impact of gender related education disparities on inward FDI is theoretically ambiguous, the results of empirical investigation require special attention. The analysis covers different gender related human capital measures to capture the multidimensional nature of human capital and education concerning level and type with respect to gender. Using panel data estimations, we conclude that the reduction of gender educational gaps in both sub-regions facilitates the absorption of inward FDI. It appears that gender equality might constitute a particular element of the institutional context of a country signaling devotion towards qualitative institutions shaping the overall investment environment. In this respect, policymakers should enhance gender equality in tertiary education in Western EU countries while attention should be given in gender equality in secondary education in the CEE countries.